DESIGN AND IMPLEMENTATION OF AMBIENT NOISE CANCELLATION SYSTEM USING ADAPTIVE FILTERS AND EQUALIZATION TECHNIQUES FOR SIGNAL PROCESSING APPLICATIONS - Hajare, Raju (Institute of Advanced Engineering and Science, 2020)
Signal Processing is very important as it gives us the flexibility of using same hardware Processing capabilities to different applications. Aim here is to design a Noise Cancellation system that uses adaptive filter techniques to eliminate any low frequency noise from the environment, leaving the music to play from the headphones without the noise waves. In the course of achieving this, we identify the original signal and generate the inverse without delay in all directions where noises interact and superimpose. We also demonstrate the approaches that we take on tackling the noise cancellation effects, along with results comparison.